‘Green Investing’ as an Approach to Make ‘Green Bangladesh’: the Role of Stock Exchanges - Alam, Lamia; Masoom, Muhammad Rehan (American Journal of Trade and Policy, 2018)
Manufacturing various products and delivering numerous services have its respective impacts on the environment.  Today, a range of eco-friendly economic instruments available worldwide, such as the eco-investment, green stocks, green investment, green banking, green bonds, green savings accounts, green mutual funds, green money market accounts and green certificates of deposit that have gained the positive reputation among many investors in the stock markets. Green investments are directed by corporations that invest in businesses committed to the environment. Some of these businesses either implement entire energy practices or good waste management systems. In the past, very few companies could have been called eco-friendly, along with several nations ensuring their support for the environment and creating environment-friendly policies, several companies have come forth with a clear objective of being responsive to the environment and lessen emissions. Bangladeshi mutual funds have not really presented much achievement in the green fund arena through the global counterparts is working in this sector. In this context, this paper intends to attract the attention of corporations towards green investments, which are effective for safe-environment and protection to earth. This paper focuses on various green investments and green investing companies in Bangladesh, and the primary focuses are:  (1) to acquaint with nature of the companies involved in green funds and green investing, (2) to make an overview of different global green investing arrangements, (3) to suggest Bangladeshi companies to come forward in green investing to make Bangladesh green and pollution-free.
Keywords: Business Ethics; Green funds; green investments; green portfolio; social responsibility